Optimal transport theory based GAN for medical image augmentation and classification - Siddiki Shan, Md. Abdul Kahhar; Quaiyum, Md. Abdul; Saha, Sugata; Nayer Anik, S. M. Navin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.